2003
DOI: 10.1007/s00170-002-1517-6
|View full text |Cite
|
Sign up to set email alerts
|

The process modelling of epoxy dispensing for microchip encapsulation using fuzzy linear regression with fuzzy intervals

Abstract: Epoxy dispensing is a popular way to perform microchip encapsulation for chip-on-board (COB) packages. However, the determination of the proper process parameters setting for a satisfactory encapsulation quality is difficult due to the complex behaviour of the encapsulant during the dispensing process and the inherent fuzziness of epoxy dispensing systems. Sometimes, the observed values from the process may be irregular. In conventional regression models, deviations between the observed values and the estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…However, previous studies also found that the performance of a developed neural network is quite dependent on the training algorithm used, the neural network architectural design as well as on the setting of the neural network parameters. Ip, Kwong, Bai, and Tsim (2003) have attempted the modeling of fluid dispensing using fuzzy regression with fuzzy intervals. In Kwong's recent work, fuzzy regression-based process models for epoxy dispensing were developed by which optimal setting of process parameters can be determined with the use of fuzzy linear programming techniques (Kwong & Bai, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies also found that the performance of a developed neural network is quite dependent on the training algorithm used, the neural network architectural design as well as on the setting of the neural network parameters. Ip, Kwong, Bai, and Tsim (2003) have attempted the modeling of fluid dispensing using fuzzy regression with fuzzy intervals. In Kwong's recent work, fuzzy regression-based process models for epoxy dispensing were developed by which optimal setting of process parameters can be determined with the use of fuzzy linear programming techniques (Kwong & Bai, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Based on P-FR, the estimated interval on the generated fuzzy linear model is influenced by all training data and the generated fuzzy linear model is robust in the presence of outliers. P-FR has been used in modelling the transfer moulding for microchip encapsulation in electronic packaging (Ip et al 2003b). (c) Chang's fuzzy regression (C-FR) (Chang 2001), which can generate fuzzy regression model in which the fuzzy coefficients can address both fuzziness and randomness of the experimental data.…”
Section: Implementation Of the Hybrid Swarm Intelligence Algorithmmentioning
confidence: 99%
“…Lai and Chang [28] applied fuzzy linear regression to model the die casting process. Ip et al [16] used fuzzy linear regression to develop a process model for epoxy dispensing. Modeling of transfer molding using fuzzy linear regression was also reported by Ip et al [17].…”
Section: Introductionmentioning
confidence: 99%